Diffusion-weighted MRI in the assessment of nephroblastoma: results of a multi-center trial - Hötker, Andreas; Lollert, André; Mazaheri, Yousef; Müller, Sabine; Schenk, Jens-Peter; Mildenberger, Philipp C.; Akin, Oguz; Graf, Norbert; Staatz, Gundula (Abdominal radiology, 2020)
Purpose: To assess the value of diffusion-weighted MRI in the pre-therapeutic evaluation of pediatric renal cortical tumors. Methods: This IRB-approved, retrospective multi-center study included 122 pediatric patients with 130 renal tumors, who underwent MRI including DWI before neoadjuvant chemotherapy and nephrectomy. Two radiologists independently assessed each tumor volumetrically, and apparent diffusion coefficient (ADC) values were calculated on a voxel-wise basis, including parameters derived from histogram and texture analysis. Results: Inter-reader agreement was excellent (ICC 0.717–0.975). For both readers, patients with locally aggressive tumor growth (SIOP 3 stage) or with metastases (M1) had significantly lower 12.5th-percentile ADC values (p ≤ 0.028) compared to those with lower-stage tumors, and the parameter energy differed significantly between patients with M1 and those with M0 status (p ≤ 0.028). Contrast and homogeneity differed significantly between benign nephroblastomatosis and malignant nephroblastoma (p ≤ 0.045, both readers). As compared to all other subtypes, the blastemal subtype demonstrated significantly higher skewness (p ≤ 0.022, both readers) and the diffuse anaplastic subtype demonstrated significantly higher 75th-percentile ADC values (p ≤ 0.042, both readers). Conclusions: Diffusion-weighted MRI may be of value in identifying benign nephroblastomatosis and assessing nephroblastoma subtypes. Therefore, further research is warranted to assess its value in risk stratification for pediatric patients with renal tumors in the future.